2019
DOI: 10.1097/ta.0000000000002333
|View full text |Cite
|
Sign up to set email alerts
|

Shock index and pulse pressure as triggers for massive transfusion

Abstract: BACKGROUND Hemorrhage is the most common cause of preventable death in trauma patients. These mortalities might be prevented with prehospital transfusion. We sought to characterize injured patients requiring massive transfusion to determine the potential impact of a prehospital whole blood transfusion program. The primary goal of this analysis was to determine a method to identify patients at risk of massive transfusion in the prehospital environment. Many of the existing predictive models require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 17 publications
0
40
0
2
Order By: Relevance
“…The 2020 CoSTR for PLS addresses the topic of graded volume resuscitation for infants and children with traumatic haemorrhagic shock as well as management of the child with cardiac arrest after trauma. The ScopRev on graded volume resuscitation identified a single observational study in the prehospital setting assessing the volume of fluid given to children with traumatic injuries, 44 with an additional 4 studies comparing total crystalloid volume given over 24 hours 45 , 46 , 47 , 48 and 1 study evaluating the volume of crystalloids given to children who needed transfusion. 49 The task force agreed that the evidence was sufficient to consider a SysRev in the near future.…”
Section: Pediatric Life Support (Basic and Advanced)mentioning
confidence: 99%
“…The 2020 CoSTR for PLS addresses the topic of graded volume resuscitation for infants and children with traumatic haemorrhagic shock as well as management of the child with cardiac arrest after trauma. The ScopRev on graded volume resuscitation identified a single observational study in the prehospital setting assessing the volume of fluid given to children with traumatic injuries, 44 with an additional 4 studies comparing total crystalloid volume given over 24 hours 45 , 46 , 47 , 48 and 1 study evaluating the volume of crystalloids given to children who needed transfusion. 49 The task force agreed that the evidence was sufficient to consider a SysRev in the near future.…”
Section: Pediatric Life Support (Basic and Advanced)mentioning
confidence: 99%
“…Seven retrospective pediatric studies were identified. [41][42][43][44][45][46][47] All were derived from trauma registries. Only 1 study assessed the volume of fluid given to children with traumatic injuries in the prehospital setting.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…For the critical outcome of survival to discharge, 4 studies found no benefit associated with graded/limited volume administration compared with standard care. 41,44,46,47 One study reported lower survival to hospital discharge associated with high-volume crystalloid administration (greater than 60 mL/kg per 24 hours) compared with low-and moderate-volume crystalloid administration (ie, 0-40 mL/kg per 24 hours or 40-60 mL/kg per 24 hours), 42 and 1 reported lower survival rates associated with higher administered crystalloid volumes (ie, greater than 150 mL/kg per 24 hours compared with 150 mL/kg or less per 24 hours) among those receiving massive transfusions. 43 Five studies reported an increased hospital or intensive care length of stay associated with higher crystalloid volume administration in the first 24 hours.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…For the critical outcome of survival to discharge, 4 studies found no benefit associated with graded/limited volume administration compared with standard care. 41 , 44 , 46 , 47 One study reported lower survival to hospital discharge associated with high-volume crystalloid administration (greater than 60 mL/kg per 24 hours) compared with low- and moderate-volume crystalloid administration (ie, 0–40 mL/kg per 24 hours or 40–60 mL/kg per 24 hours), 42 and 1 reported lower survival rates associated with higher transfusion volumes (ie, greater than 50 mL/kg per 24 hours compared with those receiving 150 mL/kg or less per 24 hours). 43 Five studies reported an increased hospital or intensive care length of stay associated with higher crystalloid volume administration in the first 24 hours.…”
Section: Pals: Recognition and Prearrest Treatments For Shockmentioning
confidence: 99%
“… 43 Five studies reported an increased hospital or intensive care length of stay associated with higher crystalloid volume administration in the first 24 hours. 42 , 43 , 44 , 46 , 47 All studies were retrospective, and they reported different interventions on differing patient populations and differing associated outcomes. Although it is difficult to compare results, there is a suggestion of a possible advantage of using limited volume resuscitation.…”
Section: Pals: Recognition and Prearrest Treatments For Shockmentioning
confidence: 99%